Kajian Metode Pelilinan Terhadap Umur Simpan Buah Manggis (Garcinia mangostana) Semi-Cutting dalam Penyimpanan Dingin - Usman Ahmad; Emmy Darmawati; Nur Rahma Refilia (Institut Pertanian Bogor, 2014)
Mangosteen can be stored for a relatively long period in low temperature storage, but peel hardening due to lostof moisture makes it difficult to open before consumption. One attempt to solve this problem is the application ofsemi-cutting treatment before storage of the fruits at low temperature. However, semi-cutting will acceleratedeterioration process since it increases fruit respiration and creates a door to microorganism to enter and spoil thefruit. Waxing the fruit after semi-cutting helps to overcome the problems, so the fruit can be stored at lowtemperature for long period, but it can be opened easily before consumption. This research aims to find a suitablemethod of waxing as well as the best wax concentration solution for waxing process. The methods of waxingconducted in this research were dipping and smearing, while the wax concentration in solution for both methodswere 6, 9, and 12%. The results show that smearing the fruit after semi-cutting with 12% wax concentration gave thelongest self life for the mangosteen stored at low temperature, while the fruits were still easier to open afterstorage.